Alkylresorcinols as a New Type of Gut Microbiota Regulators Influencing Immune Therapy Efficiency in Lung Cancer Treatment - Aleksandr V. Shestopalov; Oleg I. Kit; Anastasia A. Zabolotneva; Elena Y. Zlatnik; Aleksey Yu Maksimov; Inna A. Novikova; Alexander B. Sagakyants; Sofya V. Timofeeva; Anna S. Goncharova; Anastasia V. Galina; Svetlana A. Appolonova; Pavel A. Markin; et al. (Advanced Gut & Microbiome Research)
Background. Alkylresorcinols (ARs) are polyphenolic compounds of microbial origin with a wide spectrum of biological activities and are potentially involved in host immune functioning. The present study is aimed at evaluating alterations in AR content in blood serum and faeces from healthy donors and patients with lung cancer in connection with response to immune checkpoint inhibitor (ICI) therapy to estimate the regulatory potential of AR. Methods. Quantitative analysis of AR levels, as well as other microbial metabolites in blood serum and faeces, was performed using gas chromatography with mass spectrometric detection; estimation of lymphocyte subsets was performed by flow cytometry; faecal microbiota transplantation (FMT) from lung cancer patients after ICI therapy to germ-free mice was performed to explore whether the intestinal microbiota could produce AR molecules. Results. AR concentrations in both faeces and serum differ dramatically between healthy and lung cancer donors. The significant increase in AR concentrations in mouse faeces after FMT points to the microbial origin of ARs. For several ARs, there were strong positive and negative correlations in both faeces and serum with immune cells and these interrelationships differed between the therapy-responsive and nonresponsive groups. Conclusions. The content of ARs may influence the response to ICI therapy in lung cancer patients. ARs may be considered regulatory molecules that determine the functioning of antitumor immunity.